2009
DOI: 10.1093/jxb/erp011
|View full text |Cite
|
Sign up to set email alerts
|

Activity of tonoplast proton pumps and Na+/H+ exchange in potato cell cultures is modulated by salt

Abstract: The efficient exclusion of excess Na from the cytoplasm and vacuolar Na(+) accumulation are the main mechanisms for the adaptation of plants to salt stress. This is typically carried out by transmembrane transport proteins that exclude Na(+) from the cytosol in exchange for H(+), a secondary transport process which is energy-dependent and driven by the proton-motive force generated by plasma-membrane and tonoplast proton pumps. Tonoplast enriched-vesicles from control and 150 mM NaCl-tolerant calli lines were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 77 publications
7
53
0
Order By: Relevance
“…A control step enhancing transcription or protein translation rates and/or diminishing the turnover of the protein is most likely involved in the S. tuberosum cells in response to salt. 35 Similarly, an increased accumulation of the 68 kDa V-H + -PPase catalytic subunit in vacuolar membrane vesicles isolated from Salicornia bigelovii grown in 200 mM NaCl was observed. 46 In tonoplast vesicles from wheat (Triticum aestivum) roots exposed to severe NaCI stress (200 mmol/L) for 3 days the strong reduction in V-H + -PPase substrate hydrolysis activity correlated with lower amounts of V-H + -PPase protein.…”
Section: Regulation Of V-h + -Ppase and V-h + -Atpase Activity By Saltmentioning
confidence: 86%
See 4 more Smart Citations
“…A control step enhancing transcription or protein translation rates and/or diminishing the turnover of the protein is most likely involved in the S. tuberosum cells in response to salt. 35 Similarly, an increased accumulation of the 68 kDa V-H + -PPase catalytic subunit in vacuolar membrane vesicles isolated from Salicornia bigelovii grown in 200 mM NaCl was observed. 46 In tonoplast vesicles from wheat (Triticum aestivum) roots exposed to severe NaCI stress (200 mmol/L) for 3 days the strong reduction in V-H + -PPase substrate hydrolysis activity correlated with lower amounts of V-H + -PPase protein.…”
Section: Regulation Of V-h + -Ppase and V-h + -Atpase Activity By Saltmentioning
confidence: 86%
“…Evidence for a decreased activity of V-H + -PPase with exposure to NaCl has been described several times, [37][38][39][40][41][42] but it has been shown that the activity of V-H + -PPase increases in several plants grown within saline environments. 35,[43][44][45][46] In salt adapted cell line of Solanum tuberosum, the activity of V-H + -PPase increased about threefold over cells cultivated in the absence of salt. 35 In the halophyte Suaeda salsa only in the case of 0.1 M NaCl treatment was V-H + -PPase markedly increased over the entire duration of the experiment, all other treatments only led to a small transient increase of V-H + -PPase activity or to a decrease of activity compared to controls; thus, under salt stress and osmotic stress conditions in S. salsa, V-H + -PPase activity seems to be less important physiologically than V-H + -ATPase activity.…”
Section: Regulation Of V-h + -Ppase and V-h + -Atpase Activity By Saltmentioning
confidence: 99%
See 3 more Smart Citations